Estimation of sediment yield from Kuantan river basin using modified universal soil loss equation (musle) - Tan, Weicheng (2018)
The water in the form of rain is the main cause which accelerates the soil erosion rate on the ground which become sediment yield. The purpose of this study is to estimate the sediment yield from Kuantan river basin using the Modified Universal Soil Loss Equation (MUSLE) mathematical model. A series of data were collected to get the parameters of runoff volume (V), peak discharge (Qp), soil erodibility factor (K). ArcGIS software was utilized to obtain the topographic factor (LS), erosion control practice factor (P) and cover management factor (C). With all the relevant data, the sediment yield from Kuantan sub-river basin was computed using the MUSLE mathematical model equation. Sediment yield from Kuantan River Basin in year 2015 and 2035 was compared. And he sub-basins that contain highest and lowest amount of sediment yield in both years determined. Riau sub-basin has the highest amount of sediment yield in year 2015 and 2035 with the amount of 32750.24 tons/yr and 2764.09 tons/yr respectively. Conversely, Sungai Isap sub-basin has lowest amount of sediment yield in both years with the amount of 1.5653 tons/yr in year 2015 and 0.5177 tons/yr in year 2035.